Batari Training (Batik Gutta Tamarind and Ecoprinting) to Improve Vocational Skills of Learners at Anavah Homeschooling - Anik Agustin; Bagas Setyo Ari Widodo; Danang Aji Prayogo; Elfrida Wijayanti; Lu’lu’atur Rizky Fajriyah; Rahmat Alfan Salsabil; Rokhima Tyas Briliatna; Sabila Pratiwi; Ranti Novianti; Ediyanto (Jurnal Pengabdian Masyarakat Formosa, 2023)
The gutta tamarind batik technique is a working technique that utilizes the tamarind seed spice plant as its medium.  While Ecoprinting is making textile products using natural materials as patterns and colors used on fabric media. The idea of this research comes from training for the application of the value of Batari Art (Batik Gutta Tamarin and Ecoprint) as a strategy to increase competitiveness and vocational skills at Anavah Homeschooling, the training in its implementation can be further refined to train vocational skills in arm muscle strength and motor skills of students when carrying out training activities. Based on the results of the training outcomes, it can be concluded that BATARI training can be used to increase arm muscle strength and motor skills of students at Anavah Homeschooling.